Nasoendoscopy of velopharynx before and during diagnostic therapy - Pegoraro-Krook, Maria Inês; Dutka-Souza, Jeniffer De Cassia Rillo; Marino, Viviane Cristina De Castro [UNESP] (FapUNIFESP (SciELO), 2008)
Nasoendoscopy is an important tool for assessing velopharyngeal function. The purpose of this study was to analyze velar and pharyngeal wall movement and velopharyngeal gap during nasoendoscopic evaluation of the velopharynx before and during diagnostic therapy. Nasoendoscopic recordings of 10 children with operated cleft lip and palate were analyzed according to the International Working Group Guidelines. Ratings of movement of velum and pharyngeal walls, and size, location and shape of gaps were analyzed by 3 speech-language pathologists (SLPs). Imaging was obtained during repetitions of the syllable /pa/ during a single nasoendoscopic evaluation: (a) before diagnostic therapy, and (b) after the children were instructed to impound and increase intraoral air pressure (diagnostic therapy). Once the patients impounded and directed air pressure orally, the displacement of the velum, right, left and posterior pharyngeal walls increased 40, 70, 80, and 10%, respectively. Statistical significance for displacement was found only for right and left lateral pharyngeal walls. Reduction in gap size was observed for 30% of the patients and other 40% of the gaps disappeared. Changes in gap size were found to be statistically significant between the two conditions. In nasoendoscopic assessment, the full potential of velopharyngeal displacement may not be completely elicited when the patient is asked only to repeat a speech stimulus. Optimization of information can be done with the use of diagnostic therapy's strategies to manipulate VP function. Assuring the participation of the SLP to conduct diagnostic therapy is essential for management of velopharyngeal dysfunction.
Keywords: Diagnostic therapy; Gap size; Nasoendoscopy; Pharyngeal walls displacement; Velar displacement